Assessing the impact of Dravet syndrome on caregivers’ quality of life and perceived burden in Poland - Jan Domaradzki; Dariusz Walkowiak; Association for People with Severe Refractory Epilepsy DRAVET.PL (BMC Psychology)
Abstract Background Dravet syndrome (DS) is a rare, severe, genetically-based epilepsy that begins in infancy. Due to the multiplicity, severity, and treatment-refractory seizures, DS patients are at high risk of status epilepticus and premature death. They also experience many other symptoms and comorbidities affecting their life. This study aimed to assess the impact of DS on caregivers’ quality of life and perceived burden using Polish versions of standardized tools – the WHO Quality of Life-BREF and the Zarit Burden Interview. Methods We conducted an anonymized, self-administered, web-based survey with 106 caregivers of persons with DS with the help of the Association for People with Severe Refractory Epilepsy DRAVET.PL. Results This study shows that DS caregivers’ quality of life is generally poor and significantly lower than the national average. Specifically, most DS caregivers scored below the mean country score in all four WHOQOL-BREF domains: 87.7% scored below the mean in the social domain, 84.9% in the physical domain, 77.4% in the environmental domain, and 73.6% in the psychological domain. A significant correlation between various quality-of-life domains was observed, as well as a significant negative correlation between caregivers’ self-assessed quality of life and their perceived caregiver burden. Lower quality of life and higher burden were also associated with caregivers’ poor financial well-being. Caregivers’ experiences further varied by sex, education, employment status, place of residence, and declared religiosity. Conclusions Since caring for a DS person affects every dimension of caregivers’ lives, decreases their quality of life, and increases the feeling of burden while caring for DS patients, healthcare professionals should also monitor caregivers’ physical, mental and emotional well-being. An integrated care system that includes the entire DS family should be created.